PENYULUHAN MITIGASI BULLYING DAN KEKERASAN ANAK DIBAWAH UMUR DI LINGKUNGAN PESANTREN WILAYAH KEDIRI - Fatmah; Aina ‘Ainaul Mardliyah Anwar; Amik Nadziroh; Samsul Munir; Iwan Sulaiman; Fardizia Putri Alia; Fitriana Herawati (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2025)
Pesantren as an Islamic educational institution faces serious challenges in addressing acts of violence, especially bullying committed by children against other children. This Community Service Program aims to provide legal advocacy and education to students and pesantren management regarding legal protection for both perpetrators and victims of bullying. Through outreach and training involving professionals from various fields, this PKM provides understanding to the target partners, namely the administrators and leaders of pesantren in Kediri Regency and City, about preventive and repressive legal mechanisms for criminal acts of bullying and abuse, as well as efforts to create a child-friendly and conducive educational environment. The program also promotes a legal awareness culture based on pesantren values, supporting the creation of a safe, comfortable, and harmonious learning atmosphere. With a participatory approach, this PKM is expected to reduce violence and foster legal awareness within the pesantren community, to create a legally conscious pesantren environment focused on sustainable character development of the students